High‐sensitivity cardiac troponin T 30 days all‐come mortality in patients with acute heart failure. A Propensity Score‐Matching Analysis Based on the EAHFE Registry. TROPICA4 Study. (15th May 2020) - Roset, Alex; Jacob, Javier; Herrero‐Puente, Pablo; Alquézar, Aitor; Martín‐Sanchez, Francisco Javier; Llorens, Pere; Gil, Victor; Cabello, Irene; Richard, Fernando; Garrido, Jose Manuel; Gil, Cristina; Llauger, Lluis; et al.
Abstract: Background: Acute heart failure (AHF) patients with high troponin levels have a worse prognosis. High‐sensitive troponin T (hs‐TnT) has been used as a tool to stratify prognosis in many scales but always as a qualitative and not as a quantitative variable. Objectives: The main objective of this study was to determine the best hs‐TnT cut‐off for prediction of 30‐day all‐cause mortality. Methods: The EAHFE registry, a prospective follow‐up cohort of patients with AHF, was analysed. We performed a propensity score analysis of the optimal hs‐TnT cut‐off point previously determined by receiver operating characteristic (ROC) curve analysis. Results: Of the 13 791 patients in the EAHFE cohort, we analysed 3190 patients in whom hs‐TnT determination was available. The area under the ROC curve for 30‐day all‐cause mortality was 0.70 (CI95% 0.68 to 0.71; P  < .001), establishing an optimal cut‐off of hs‐TnT of 35 ng/L. The sensitivity and specificity of this cut‐off were 76.2 and 55.5%, respectively, with a negative predictive value (NPV) of 95.3%. A propensity score was made with 34 variables showing differences based on the cut‐off of 35 ng/L for hs‐TnT. In the analysis of the population obtained with the propensity score, patients with hs‐TnT > 35 ng/L showed a greater 30‐day all‐cause mortality, with a HR of 2.95 (CI95% 1.83‐4.75; P  < .001). External validation reported similar results. Conclusions: An hs‐TnT value of 35 ng/L is an adequate cut‐off to evaluate the prediction of 30‐day all‐cause mortality with a NPV of 95.3%.